Isolation and characterization of yogurt starter cultures from traditional yogurts and growth kinetics of selected cultures under lab-scale fermentation - Cakmakoglu, Selma Kayacan; Vurmaz, Melike; Bezirci, Emine; Kaya, Yasemin; Dikmen, Hilal; Goktas, Hamza; Demirbas, Fatmanur; Encu, Betul; Soykut, Esra Acar; Alemdar, Filiz; Cakir, Ibrahim; Durak, M. Zeki; et al. (TAYLOR & FRANCIS INC, 2023)
The development of new starter cultures is a crucial task for the food industry to meet technological requirements and traditional products are important reservoirs for new starter cultures. In this respect, this study aimed to isolate, identify, and determine the technological characteristics of Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus strains originated from traditional yogurt samples. Genotypic discrimination of 200 isolates revealed the presence of distinct 19 S. thermophilus and 11 Lb. delbrueckii subsp. bulgaricus strains as potential starter cultures. Strain-specific properties determined the acidification capacity of the yogurt starter cultures and a higher acidification capacity was observed for S. thermophilus strains compared to Lb. delbrueckii subsp. bulgaricus strains. Proteolytic activity was found between 0.012-0.172 and 0.078-0.406 for S. thermophilus and Lb. delbrueckii subsp. bulgaricus strains, respectively. 4 of S. thermophilus and 3 of Lb. delbrueckii subsp. bulgaricus strains were found resistant to all tested bacteriophages. The antibiotic susceptibility tests of the isolates revealed that a very low antibiotic resistance was observed for the yogurt starter cultures. Finally, the growth kinetics of selected strains were determined and the maximum specific growth rate of selected S. thermophilus and Lb. delbrueckii subsp. bulgaricus was calculated as 0.527 h(-1) and 0.589 h(-1), respectively.
Keywords: Growth kinetics; Lb; delbrueckii subsp; bulgaricus; S; thermophilus; yogurt starter culture; LACTIC-ACID BACTERIA; DELBRUECKII SSP BULGARICUS; STREPTOCOCCUS-THERMOPHILUS; IDENTIFICATION; STRAINS; PHTHALDIALDEHYDE; TEMPERATURE; PROTEOLYSIS; SOURDOUGH; PHAGES; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology